Uptake and intracytoplasmic storage of pigmented particles by human CD34+ stromal cells/telocytes: endocytic property of telocytes. Issue 12 (30th September 2014) - Díaz‐Flores, Lucio; Gutiérrez, Ricardo; García, Mª Pino; Sáez, Francisco J.; Aparicio, Fernando; Díaz‐Flores, Lucio; Madrid, Juan F.
Abstract We studied the phagocytic‐like capacity of human CD34+ stromal cells/telocytes (TCs). For this, we examined segments of the colon after injection of India ink to help surgeons localize lesions identified at endoscopy. Our results demonstrate that CD34+ TCs have endocytic properties (phagocytic‐like TCs: phTCs), with the capacity to uptake and store India ink particles. phTCs conserve the characteristics of TCs (long, thin, bipolar or multipolar, moniliform cytoplasmic processes/telopodes, with linear distribution of the pigment) and maintain their typical distribution. Likewise, they are easily distinguished from pigment‐loaded macrophages (CD68+ macrophages, with oval morphology and coarse granules of pigment clustered in their cytoplasm). A few c‐kit/CD117+ interstitial cells of Cajal also incorporate pigment and may conserve the phagocytic‐like property of their probable TC precursors. CD34+ stromal cells in other locations (skin and periodontal tissues) also have the phagocytic‐like capacity to uptake and store pigments (hemosiderin, some components of dental amalgam and melanin). This suggests a function of TCs in general, which may be related to the transfer of macromolecules in these cells. Our ultrastructural observation of melanin‐storing stromal cells with characteristics of TCs (telopodes with dichotomous branching pattern) favours this possibility. In conclusion, intestinal TCs have a phagocytic‐like property, a function that may be generalized to TCs in other locations. This function (the ability to internalize small particles), together with the capacity of these cells to release extracellular vesicles with macromolecules, could close the cellular bidirectional cooperative circle of informative exchange and intercellular interactions.